SREBP-1 transcription factors regulate skeletal muscle cell size by controlling protein synthesis through myogenic regulatory factors. - Kevin Dessalle; Vanessa Euthine; Stéphanie Chanon; Joffrey Delarichaudy; Isao Fujii; Sophie Rome; Hubert Vidal; Georges Nemoz; Chantal Simon; Etienne Lefai (PLoS ONE, 2012)
SREBP-1 are ubiquitously expressed transcription factors, strongly expressed in lipogenic tissues where they regulate several metabolic processes like fatty acid synthesis. In skeletal muscle, SREBP-1 proteins regulate the expression of hundreds of genes, and we previously showed that their overexpression induced muscle atrophy together with a combined lack of expression of myogenic regulatory factors. Here we present evidences that SREBP-1 regulate muscle protein synthesis through the downregulation of the expression of MYOD1, MYOG and MEF2C factors. In myotubes overexpressing SREBP-1, restoring the expression of myogenic factors prevented atrophy and rescued protein synthesis, without affecting SREBP-1 action on atrogenes and proteolysis. Our results point out the roles of MRFs in the maintenance of the protein content and cell size in adult muscle fibre, and contribute to decipher the mechanisms by which SREBP-1 regulate muscle mass.